Knowledge Management The Development Of State Civil Apparatus In Polewali Mandar Regency, West Sulawesi Province - Tri Ayu Hardiyanti; Fernandes Simangunsong; Layla Kurniawati (Jurnal Scientia, 2024)
The aim of this research is to find out and analyze Knowledge Management in the Development of the State Civil Apparatus, find out and analyze the supporting and inhibiting factors of Knowledge Management in the Development of the State Civil Apparatus in Polewali Mandar Regency, West Sulawesi Province. The theory used as an analytical tool in writing this thesis is Nonaka and Takeuchi's theory in Nawawi (2010) which explains that knowledge management requires 4 (four) stages (known as SECI), namely "Socialization, Externalization, Combination, and Internalization". The method used is a qualitative approach by collecting interview techniques, observation and documentation. The data analysis technique in this research involves several stages, namely data reduction, data presentation and conclusions. The informant in the research was PJ. Regent of Polewali Mandar, Member of Commission 2 of the DPRD of Polewali Mandar Regency, Regional Secretary of Polewali Mandar Regency, Assistant 1 for Government of the Regional Secretariat of Polewali Mandar Regency, Head of BKAD of Polewali Mandar Regency, Head of the Communication and Information and Encryption Service of Polewali Mandar Regency, Head of Balitbangren Polewali Mandar Regency, Inspector of the Regency Inspectorate Polewali Mandar, Head of the Polewali Mandar Regency Education and Training Personnel Agency, Secretary of the Polewali Mandar Regency Education and Training Personnel Agency, Head of the Adminpeg Division of the Polewali Mandar Regency Education and Training Personnel Agency, Head of the Training Division of the Polewali Mandar Regency Education and Training Personnel Agency, Head of the PIK Division Polewali Mandar Regency Education and Training Personnel Agency, Human Resources Analysis of Young Expert Apparatus at Polewali Mandar Regency Education and Training Personnel Agency, and Polewali Mandar Regency Education and Training Personnel Agency Staff. Based on the results of research in the field, it shows that Knowledge Management in the Development of State Civil Apparatus in Polewali Mandar Regency has not been implemented optimally due to the lack of availability of human resources, low budgets, and regulations related to knowledge management have not been implemented well in the Regional Government of Polewali Mandar Regency.